Difficult decisions : how leaders make the right call with insight, integrity, and empathy - Pliner, Eric (Ascent Audio, 2022)
What do you do when the algorithm doesn't have the answer? Countless tools and frameworks claim to make decisions objective and bias-free. But in reality, the defining decisions that leaders face are complex ones with subjective information sources and conflicting courses of action. That's why the toughest choices are left to the leaders, and that's why formulas won't answer them. In Difficult Decisions: How Leaders Make the Right Call with Insight, Integrity, and Empathy, leadership expert and CEO of YSC Consulting, Eric Pliner, delivers a set of practical tools for listeners to make sense of these complex, subjective decisions quickly and with integrity. It presents a path to understanding your own subjectivity, and how your morals, ethics, and responsibilities affect how leaders make the most important decisions. Difficult Decisions is ideal for executives, managers, and business leaders to examine their own intuition and navigate the most conflicted choices they make. It's a challenging listen and an indispensable resource to help listeners develop self-reflection, clarify their values, and ultimately make the choice that is most "right" to them